Reaching for the brain: stimulating neural activity as the big leap in optic nerve regeneration - GeeraertsEmiel; MoonsLieve; De GroefLies (眼科学报, 2016)
In the August issue of Nature Neuroscience , Lim and co-workers reported on their study of axonal regeneration in the adult optic nerve, revealing that combined activation of mammalian target of rapamycin (mTOR) signaling and enhancing neural activity leads to successful restoration of axonal trajectories to visual brain centers (1). Here, we shed light on their breakthrough findings and how these may represent a major leap forward in the search for novel strategies for central nervous system (CNS) repair.